2022
DOI: 10.3390/antiox11101879
|View full text |Cite
|
Sign up to set email alerts
|

Kelulut Honey Ameliorates Oestrus Cycle, Hormonal Profiles, and Oxidative Stress in Letrozole-Induced Polycystic Ovary Syndrome Rats

Abstract: Kelulut honey (KH) has been proven to have excellent antioxidative and anti-inflammatory properties with unique physicochemical characteristics. Therefore, we investigated the isolated and combined effects of KH, metformin, or clomiphene in alleviating oxidative stress and reproductive and metabolic abnormalities in polycystic ovary syndrome (PCOS). Female Sprague-Dawley (SD) rats were given 1 mg/kg/day of letrozole for 21 days to induce PCOS. PCOS rats were then divided into six treatment groups: untreated, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…It has been reported that hyperandrogenism is the main factor that contributes to aromatase deficiency in women with PCOS [ 10 ]. Previously, KH was shown to reduce hyperandrogenism in PCOS rats [ 36 ] which might explain its role in restoring the aromatase expression in this study. However, the specific molecular pathway mediated by KH remains to be elucidated.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…It has been reported that hyperandrogenism is the main factor that contributes to aromatase deficiency in women with PCOS [ 10 ]. Previously, KH was shown to reduce hyperandrogenism in PCOS rats [ 36 ] which might explain its role in restoring the aromatase expression in this study. However, the specific molecular pathway mediated by KH remains to be elucidated.…”
Section: Discussionmentioning
confidence: 58%
“…These results further validate our preliminary study findings on KH’s beneficial effect on PCOS rats’ ovarian histology [ 39 ]. Previously, KH was reported to improve oxidative stress status and normalise the hormonal and oestrus cycle disturbances in PCOS-induced rats [ 36 ]. These hormonal and oestrus cycle corrections bring back physiological healthy folliculogenesis, which is manifested by improvement in folliculogenesis-related factors and histology findings in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations